1995
DOI: 10.1210/endo.136.10.7664696
|View full text |Cite
|
Sign up to set email alerts
|

Subdiaphragmatic vagotomy suppresses endotoxin-induced activation of hypothalamic corticotropin-releasing hormone neurons and ACTH secretion.

Abstract: In order to assess the possibility that endotoxin-induced activation of the hypothalamus-pituitary-adrenal (HPA) axis is mediated by vagal afferents, we studied the effects of transection of the vagal nerves on endotoxin-induced Fos expression in hypothalamic corticotropin-releasing hormone (CRH) neurons and plasma ACTH and corticosterone responses. Groups of rats were subjected to sham surgery, complete subdiaphragmatic vagotomy (SVGX), or selective transection of the hepatic branch (HVGX). Two weeks after su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
81
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(85 citation statements)
references
References 9 publications
3
81
0
Order By: Relevance
“…Vagal sensory input from the abdomen implicated in the central neural (Wan, et al, 1994), hyperthermic , and hormonal (Fleshner, et al, 1995;Gaykema, et al, 1995;Kapcala, et al, 1996) responses to inflammatory stimuli may have contributed to this response as may the action of circulating mediators on the area postrema (Cunningham et al, 1994). However, Fos appeared in this circumventricular organ only in the rats with the most intense dorsomedullary responses as reported previously during acute inflammation Ericsson, et al, 1994).…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Vagal sensory input from the abdomen implicated in the central neural (Wan, et al, 1994), hyperthermic , and hormonal (Fleshner, et al, 1995;Gaykema, et al, 1995;Kapcala, et al, 1996) responses to inflammatory stimuli may have contributed to this response as may the action of circulating mediators on the area postrema (Cunningham et al, 1994). However, Fos appeared in this circumventricular organ only in the rats with the most intense dorsomedullary responses as reported previously during acute inflammation Ericsson, et al, 1994).…”
Section: Discussionsupporting
confidence: 55%
“…This surgical model mirrors the clinical course of sepsis and recreates a sequence of events that differs from that after a lethal dose of endotoxin in both time course and the release and distribution of inflammatory mediators (Mathiak, et al, 2000;Wichterman, et al, 1980). The presence of peritonitis and a surgically induced cecal abscess in the model may constitute a sustained stimulus to visceral sensory pathways that respond to tissue inflammation (Fleshner et al, 1995;Gaykema, et al, 1995;Kapcala et al, 1996;Wan, et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These pieces of evidence suggest that the CeA response is independent of prostaglandin synthesis mechanisms and presumably reliant either on the production of other secondary signaling molecules or alternatively afferent pathways originating at the level of the NTS cells. With regard to the latter, systemic IL-1␤ signals might reach the NTS by means of visceral sensory afferents (Fleshner et al, 1995;Gaykema et al, 1995;Kapcala et al, 1996;Goehler et al, 1997;Ishizuka et al, 1997;Ek et al, 1998), although it remains to be investigated whether circulating IL-1␤-induced CeA cell recruitment depends on the activation of vagal afferent fibers.…”
Section: Putative Mechanisms For Cea Cell Recruitment By Systemic Il-1␤mentioning
confidence: 99%
“…For instance, endotoxin from E. coli can induce 1) a fever response in rabbits when administered intracerebroventricularly (16), and 2) activation of hypothalamic histaminergic neurons in rats leading to ACTH release (17). In addition, a recent study has demonstrated that subdiaphragmatic vagotomy can suppress the endotoxin-induced activation of hypothalamic corticotropin -releasing hormone and ACTH secretion (18).…”
Section: Introductionmentioning
confidence: 99%